1987
DOI: 10.1017/s0021859600079545
|View full text |Cite
|
Sign up to set email alerts
|

The use of water-washed neem (Azadirachta indica) seed kernel cake in the feeding of buffalo calves

Abstract: A new protein supplement in the form of water-washed neem (Azadirachta indica) seed kernel cake for tropical countries such as India, Pakistan, Ceylon, Burma and also for tropical regions of Australia, Africa, the Middle East and South-East Asia which could be successfully fed to cattle has been reported by Nath, Rajgopal & Garg (1983). The adverse effect of the bitter or toxic principles contained in the neem seed kernel cake could be removed by water washing. It has a potential of providing Rs.350 millio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 1 publication
4
6
0
Order By: Relevance
“…Replacement of GNC with UTNSKC had no effect on palatability as is evident from similar intakes of concentrate offered (Table 2). This observation is similar to earlier studies where NSKC (Rajagopal and Nath, 1981), water-washed neem seed kernel cake (WWNSKC) (Agrawal et al, 1987;Nath et al, 1989) and UTNSKC (Reddy, 1992) totally replaced GNC in concentrate mixtures. Lambs offered UTNSKC consumed more hay than those on GNC resulting in higher intake of DM.…”
Section: Digestibility Studysupporting
confidence: 91%
See 4 more Smart Citations
“…Replacement of GNC with UTNSKC had no effect on palatability as is evident from similar intakes of concentrate offered (Table 2). This observation is similar to earlier studies where NSKC (Rajagopal and Nath, 1981), water-washed neem seed kernel cake (WWNSKC) (Agrawal et al, 1987;Nath et al, 1989) and UTNSKC (Reddy, 1992) totally replaced GNC in concentrate mixtures. Lambs offered UTNSKC consumed more hay than those on GNC resulting in higher intake of DM.…”
Section: Digestibility Studysupporting
confidence: 91%
“…The depression in digestibility of DM on the ration containing UTNSKC agrees with observations by Agrawal et al (1987) in buffalo calves fed a concentrate mixture containing WWNSKC. However, in other studies, no such depression was observed on feeding a concentrate mixture containing 45% NSKC (Rajagopal and Nath, 1981), 45% WWNSKC (Nath et al, 1983) or 30% UTNSKC (Reddy, 1992).…”
Section: Digestibility Studysupporting
confidence: 87%
See 3 more Smart Citations